Asymmetric volatility and macroeconomic factors on Indonesian government bond returns - Megasari, Debbie; Siregar, Hermanto; Syarifuddin, Ferry (University of Merdeka Malang, 2019)
Macroeconomic are important variables influencing volatility in the bond market. Some of the challenges faced such as default risk, liquidity risk, interest rate risk, inflation risk, and exchange rate risk. This study is aimed at examining asymmetric volatility using the EGARCH model and at estimating macroeconomic variables which influence the return of Indonesian Government bonds. The asymmetric volatility can be measured by determining the best order value of the EGARCH model. Based on the findings of the study, EGARCH (2.1) is the best model for assessing volatility in short-term SUN returns, EGARCH (3.1) for medium-term SUN and EGARCH (2.3) for the long term. The asymmetric volatility pertains in the returns of short, medium and long-term government bonds. In addition, the negative information has a greater impact than positive information in the short, medium and long term. The deposit rate and return of the Composite Stock Price Index have a significant positive effect on short, medium and long term bond returns. The effective federal funds rate or FED interest rate has a significant positive effect on the return of short and long-term SUN bonds while in the medium term it has no effect. Exchange rates have a significant negative effect on short, medium and long term bond returns.JEL Classification: D13, I31, J22DOI:Â https://doi.org/10.26905/jkdp.v23i3.2613